Features of the course and outcomes of COVID-19 in patients with axial spondyloarthritis - Sh. F. Erdes (Научно-практическая ревматология)
The 2019 coronavirus disease pandemic (COVID-19) is particularly challenging not only for doctors, but also for patients with inflammatory diseases, including spondyloarthritis. Although a large number of studies have been conducted over the past 2 years on the effect of COVID-19 on patients with rheumatic diseases, however, the conclusions from them are not always unambiguous. Given the growing number of cases of COVID-19 infection worldwide, there is a need to study the impact of individual diseases on its outcomes. The results of the study of COVID-19 in spondyloarthritis are limited to isolated reports of cases of the disease. Moreover, there is practically no literature devoted to the outcomes of COVID-19 exclusively in patients with axial spondyloarthritis. However, over the past few months, two large studies have been publishe d, in total, analyzing the outcomes of infection with SARS-CoV-2 in more than 14,000 patients with spondyloarthritis. The article discusses the results of these studies, the result of which is the conclusion that the presented data should convince both patients and doctors that axial spondyloarthritis and the therapy carried out for its treatment does not increase the risk of infection and does not aggravate the outcomes of COVID-19.